Human resources management in the children's social welfare institution darul ilmi, Depok city - Sahrul, Muhammad; Nulhaqim, Soni Akhmad; Darwis, Rudi Saprudin; Fahrudin, Adi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In every organization, including human service organizations, the role of human resources becomes very important, because the running of the organization is largely determined by the existence of human resources as a driver in resource management and organizational activities that are realized to achieve organizational goals. This study aims to examine human resource management in the setting of a child social welfare institution which is part of a human service organization. This study uses a descriptive qualitative approach. Data were obtained from primary and secondary data, while data collection techniques were carried out through observation, in-depth interviews and documentation studies. Data analysis was carried out through the stages of data presentation, data reduction, and drawing conclusions. The research location is at the Darul Ilmi Child Welfare Institution, Depok City, West Java Province. The results of the study indicate that human resources are very important in addition to other resources in child social welfare institutions because they involve management from planning to awarding staff or employees who are used as a unit in human resource management so that the realization of an effective and efficient organization can be achieved.